Thymic function recovery after unrelated donor cord blood or T-cell depleted HLA-haploidentical stem cell transplantation correlates with leukemia relapse - Clave, Emmanuel; Lisini, Daniela; Douay, Corinne; Giorgiani, Giovana; BUSSON, Marc; Zecca, Marco; Moretta, Francesca; Acquafredda, Gloria; Brescia, Letizia P.; Locatelli, Franco; Toubert, Antoine (Frontiers in Immunology, 2013)
Use of alternative donors/sources of hematopoietic stem cells (HSC), such as cord blood (CB) or HLA-haploidentical (Haplo) related donors, is associated with a significant delay in immune reconstitution after transplantation. Long-term T-cell immune reconstitution largely relies on the generation of new T cells in the recipient thymus, which can be evaluated through signal joint (sj) and beta T-cell-Receptor Excision Circles (TREC) quantification. We studied two groups of 33 and 24 children receiving, respectively, HSC Transplantation (HSCT) from an HLA-haploidentical family donor or an unrelated CB donor, for both malignant (46) and non-malignant disorders (11). Relative and absolute sj and beta-TREC values indicated comparable thymic function reconstitution at 3 and 6 months after the allograft in both groups. Compared to children with non-malignant disorders, those with hematological malignancies had significantly lower pre-transplantation TREC counts. Patients who relapsed after HSCT had a significantly less efficient thymic function both before and 6 months after HSCT with especially low beta-TREC values, this finding suggesting an impact of early intra-thymic T-cell differentiation on the occurrence of leukemia relapse.